Effects of wheat gluten hydrolysates fractionated by different methods on the growth and fermentation performances of brewer's yeast under high gravity fermentation. (25th October 2017) - Zhou, Yongjing; Yang, Huirong; Zong, Xuyan; Cui, Chun; Mu, Lixia; Zhao, Haifeng
Summary: Wheat gluten hydrolysates (WGH) were fractionated through ultrafiltration membrane with molecular weight (Mw) cut‐off of 3 kDa and ethanol precipitation, respectively. WGH and their fractions were used to examine their effects on the growth and fermentation performances of brewer's yeast under high gravity fermentation. Results showed that WGH and their fractions exhibited significant differences in biomass accumulation, viability, ethanol yield, free amino nitrogen and sugar consumptions under high gravity fermentation. Compared to WGH, the fractions with Mw < 3 kDa and the supernatant of WGH treated with ethanol precipitation showed better fermentation performance for brewer's yeast. The relatively lower molecular weight and the higher levels of Leu, Lys, His and Arg in these two fractions might be responsible for their bioactivity for brewer's yeast. Thus, both ultrafiltration and ethanol precipitation could be used as efficient methods for enriching peptides with significant growth‐ and fermentation‐promoting activity for brewer's yeast under high gravity fermentation. Abstract : WGH and their fractions treated with ultrafiltration and ethanol precipitation had significant impacts on the growth and fermentation performances of brewer's yeast during high gravity fermentation.